Vaccination against Chrysomya bezziana: a summary of current knowledge - Peter Willadseni (Indonesian Center for Animal Research and Development (ICARD), 2000)
Methods for the culture of the Old World Screwworm Fly Chrysomya bezziana on a small laboratory scale, the production of life stages and tissues suitable for vaccine study, and the in vitro and in vivo assessment of vaccine effects have all been developed. These methods would be applicable to further studies on screwworm control by many alternative technologies. It has been shown to be possible to induce dramatic immunological effects on feeding larvae and to isolate and characterise individual antigens. However, a recombinant vaccine remains elusive. Current understanding of the effects of vaccination is discussed and suggestions made for possible future research directions. Key words: Chrysomya bezziana, Old World screwworm fly, vaccine, recombinant antigen, sheep